The boy and the gorilla - Azúa Kramer, Jackie (Candlewick Press, 2020)
This profoundly moving tale about a grieving boy and an imaginary gorilla makes real the power of talking about loss. On the day of his mother's funeral, a young boy conjures the very visitor he needs to see - a gorilla. Wise and gentle, the gorilla stays on to answer the heart-heavy questions the boy hesitates to ask his father: Where did his mother go? Will she come back home? Will we all die? Yet with the gorilla's friendship, the boy slowly begins to discover moments of comfort in tending flowers, playing catch and climbing trees. Most of all, the gorilla knows that it helps to simply talk about the loss - especially with those who share your grief and who may feel alone too.